Digital transformation of the mobile connected pharmacy: a first step toward community pharmacy 5.0 - Barata, João (2022)
Community pharmacies have made significant advances in digital technology; however, mobile systems are only emerging in this sector and mostly focusing patient-centric connections. This study reveals a case of digital transformation in a mobile connected pharmacy, balancing efficient pharmaceutical services and digital innovation. A mobile connected pharmacy solution (mPharmaCare) is developed for a community of near 100.000. The first stage includes a bibliometric analysis and a structured literature review of the mobile connected pharmacy. In the second stage, action research was conducted to evaluate mPharmaCare adoption. A dual organizational structure was tested to cope with innovation and efficient exploration of pharmacy services. Community Pharmacy 5.0 is an inspiring vision that will take advantage of mobility. However, there are tensions between the core pharmacy business and the new technology layers of community connections. Community pharmacies require both client-centric and community-centric approaches to achieve individualization of patient care and horizontal and end-to-end digital integration of pharmacy data. Digital transformation can remove silos in the community pharmacy. Creating an - internal or outsourced - innovation division may be suitable for medium and large community pharmacies. Moreover, pharmacies must consider shifting to a product-service system offer, deploying synchronization mechanisms with different stakeholders.